Potentialities of Fermented Cashew Apple Bagasse with Penicillium roqueforti ATCC 10110: Total Phenolics, Antifungal Activity and Cytotoxicity (Research, Society and Development, 2022)
In this study, cashew apple (Anacardium occidentale L.) bagasse, a residue from the industrial extraction of the juice, was subjected to a solid-state fermentation process with the fungus Penicillium roqueforti ATCC 10110 and the total phenolic content was evaluated, as well as the activity of extracts against strains of dermatophyte fungi of the genera Trichophyton and Microporum; cytotoxicity was analyzed through hemolytic potential in human erythrocytes. The results showed that the fermented cashew apple bagasse had a higher content of total phenolics compared to the unfermented bagasse, a potent antifungal activity with minimum inhibitory concentrations (MIC) ranging from 256 to 512 μg/mL against the strains: T. rubrum (LM-115 and LM-629), T. mentagrophytes LM-119, M. gypseum LM-512 and M. canis (LM-68 e LM-110), with low cytotoxicity. Therefore, the fermented extracts of cashew apple bagasse can be considered as a promising natural non-toxic product for studies in the development of agents against skin diseases, especially for the treatment of dermatophytosis.